Inscriptions on the Interior of the 30th Dynasty Coffin of Nefer-renepet from Akhmim - Branislav Anđelković (University of Belgrade, 2016)
The anthropoid wooden coffin with plinth (L. 183.5 cm), datable to the mid–4th century B.C. (30th Dynasty), names Nefer-renepet, a dancer of Min from Akhmim. This object represents one of the artistically and technically superior coffins produced by Late Period Egyptian coffin workshops. It was formerly part of the Amherst collection, and was purchased by Ernest Brummer at a Sotheby, Wilkinson & Hodge auction in London in 1921, then donated the same year to the National Museum in Belgrade. The interior of the lid is distinguished by a remarkable ‘gliding Nut motif with upward streaming hair’ (an extremely important iconographic element) while the interior of the trough is dominated by a line drawing of Imentet wearing a diagonallyveined maat-feather on her head. The interior decoration includes inscriptions written on the side facets. Written hastily in whitish-yellow line on a rough ground of thick black pigment (in contrast to the fine outer decoration of the coffin) these barely legible Stundenwachen texts, are nonetheless significant, and are to be identified as abbreviated texts derived from the Book of Day and Book of Night. They are a manifestation of Late Period magical symbolism stemming from New Kingdom funerary compositions. Their presence on the coffin, however hurried, was intended to ease Nefer-renepet’s passage through the netherworld. Since 1992 the coffin of Nefer-renepet is kept in the Archaeological Collection of the Faculty of Philosophy, University of Belgrade.